2018
DOI: 10.1038/s41598-018-21229-9
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Characteristics in Patients on Haemodialysis vs. Peritoneal Dialysis

Abstract: Atrial fibrillation (AF) is highly prevalent in dialysis patients, however whether its impact differs between patients on haemodialysis (HD) vs. peritoneal dialysis (PD) is unknown. We aimed to compare the association of AF and clinical outcomes in different dialysis modalities. We performed a population based retrospective cohort study, including adult patients who initiated dialysis between the years 2002 and 2015. Clinical, echocardiographic and laboratory data were reviewed and correlated with outcomes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
2
15
0
2
Order By: Relevance
“…Another Taiwanese retrospective cohort study of 15,947 patients in 2016 showed that the incidence of AF was higher among hemodialysis patients [24]. In another study of 1,130 ESRD patients conducted in 2017, 26.9% of the cohort were noted to have AF during the study period [25]. In the present cohort, 14.5% of the incident ESRD patients had AF at the initiation of hemodialysis, confirming the high prevalence and incidence of AF in dialysis population.…”
Section: Discussionsupporting
confidence: 72%
“…Another Taiwanese retrospective cohort study of 15,947 patients in 2016 showed that the incidence of AF was higher among hemodialysis patients [24]. In another study of 1,130 ESRD patients conducted in 2017, 26.9% of the cohort were noted to have AF during the study period [25]. In the present cohort, 14.5% of the incident ESRD patients had AF at the initiation of hemodialysis, confirming the high prevalence and incidence of AF in dialysis population.…”
Section: Discussionsupporting
confidence: 72%
“…In fact, hemodialysis procedure itself has been identi ed as a trigger for AF (17). Studies comparing the incidence rate of AF in non-dialysis and dialysis patients with CKD do not exist, but AF incidence has been numerically higher in CKD patients undergoing dialysis (5,9,(11)(12)(13). One previous trial reported a higher incidence rate of AF in dialysis patients compared to healthy controls (13).…”
Section: Discussionmentioning
confidence: 99%
“…17 Incident AF in prevalent ESRD patients was also noted to be associated with increased mortality risk. 4 Therefore, AF in the presence of kidney disease deserves special attention and management.…”
Section: Epidemiology Of Af and Cva In Esrdmentioning
confidence: 99%
“…3 Larger left atrium, higher systolic blood pressure, and increased age were additional risk factors for AF. 3,4 In addition to AF, risk of stroke (event rate of 5.61 per 100 person years) in ESRD patients is greatly increased as compared to those without renal impairment (event rate of 3.61 per 100 person years), 5 which is very concerning due to the already increased CV mortality among ESRD patients.…”
Section: Introductionmentioning
confidence: 99%